2022
DOI: 10.1021/jacsau.2c00237
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Cationic Aluminoborate as a New Paradigm for Highly Selective and Efficient Cr(VI) Capture from Aqueous Solution

Abstract: Water pollutants existing in their oxyanion forms have high solubility and environmental mobility. To capture these anionic pollutants, cost-effective inorganic materials with cationic frameworks and outstanding removal performance are ideal adsorbents. Herein, we report that two-dimensional (2D) cationic aluminoborate BAC(10) sets a new paradigm for highly selective and efficient capture of Cr(VI) and other oxyanions from aqueous solution. The structure of Cr(VI)-exchanged BAC(10) sample (Cr(VI)@BAC(10), H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…However, when the pH exceeded 6, there is a significant decrease in its adsorption of CrO 4 2– ions. The decrease in CrO 4 2– adsorption with increasing pH is attributed to additional OH – competing for adsorption on 1-Tb . The adsorption experiment of OH – ions was conducted to demonstrate this, revealing that equilibrium adsorption on 1-Tb was achieved within a span of 12 h with an adsorption capacity of 36.8 mg/g (Figure S17).…”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, when the pH exceeded 6, there is a significant decrease in its adsorption of CrO 4 2– ions. The decrease in CrO 4 2– adsorption with increasing pH is attributed to additional OH – competing for adsorption on 1-Tb . The adsorption experiment of OH – ions was conducted to demonstrate this, revealing that equilibrium adsorption on 1-Tb was achieved within a span of 12 h with an adsorption capacity of 36.8 mg/g (Figure S17).…”
Section: Results and Discussionmentioning
confidence: 97%
“…The decrease in CrO 4 2− adsorption with increasing pH is attributed to additional OH − competing for adsorption on 1-Tb. 31 The adsorption experiment of OH − ions was conducted to demonstrate this, revealing that equilibrium adsorption on 1-Tb was achieved within a span of 12 h with an adsorption capacity of 36.8 mg/g (Figure S17). It was indicated that in all cases, the optimum pH for CrO 4 2− adsorption by 1-Tb was 3, so all subsequent adsorption tests were carried out at pH = 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Borates are listed as critical materials, main sources of boron, and have a wide range of industrial applications [19]. Wang et al reported the study on the effective removal of Cr(VI) by highly crystalline aluminoborate BAC (10), which was hydrothermally synthesized from a mixture of boric acid, anhydrous aluminum trichloride, and ammonium hydroxide at 150°C for 18 h [20]. However, ammonium hydroxide has the characteristics of volatility and corrosion, and it is limited in the process of use.…”
Section: Introductionmentioning
confidence: 99%